Multi-Omics Analysis Reveals Changes in the Intestinal Microbiome, Transcriptome, and Methylome in a Rat Model of Chronic Non-bacterial Prostatitis: Indications for the Existence of the Gut-Prostate Axis - Liu, Junsheng; Wang, Yihe; Zhang, Guangwen; Liu, Liu; Peng, Xichun (Frontiers in Physiology, 2022)
Chronic nonbacterial prostatitis (CNP) is one of the most prevalent diseases in human males worldwide. In 2005, the prostate-gut axis was first proposed to indicate the close relationship between the prostate and the intestine. This study investigated CNP-induced changes of the gut microbiota, gene expression and DNA methylation in a rat model by using multi-omics analysis. Firstly, 16S rDNA sequencing presented an altered structure of the microbiota in caecum of CNP rats. Then, transcriptomic analysis revealed that the expression of 185 genes in intestinal epithelium was significantly changed by CNP. These changes can participate in the immune system, digestive system, metabolic process, etc. Finally, methylC-capture sequencing (MCC-Seq) found 73,232 differentially methylated sites (DMSs) in the DNA of intestinal epithelium between control and CNP rats. A combined analysis of methylomics and transcriptomics suggested an epigenetic mechanism for CNP-induced differential expression genes correlated with intestinal barrier function, immunity, metabolism, enteric infectious disease, etc. More importantly, the transcriptomic, methylomic and gut microbial changes were highly correlated with multiple processes including intestinal immunity, metabolism and epithelial barrier function. In this study, disrupted homeostasis in the gut microbiota, gene expression and DNA methylation were reported in CNP, which supports the existence of the gut-prostate axis.